PELAKSANAAN PENGAWASAN LALU LINTAS DI KOTA PONTIANAK - Gunadi E.21110095 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this abstract is a lack of public knowledge about traffic rules and road transport, the indifference of the majority community to call police for orderly traffic. Like riding motorcycles do not use helmets, luggage rack of the motorcycle and three others, as well as the patterns of behavior of some people lack discipline in traffic. The results showed that the implementation of internal monitoring visits of inspection, testing to the investigation, had not yet effective, this is due to the inaccuracy of the time in monitoring, data is not accurate for the deviations found in the regulatory apparatus Unity Pontianak City Traffic Police. The results showed that the obstacles faced Pontianak City Police Traffic Unit in conducting preventive supervision in creating traffic safety and order is the lack of knowledge about the rules, markings and traffic signs. Supervision in creating repressive security, public order and the smooth traffic is done by Socializing About The rules of traffic, improving people's motivation for orderly traffic, and increase ticket and program effectiveness. The results showed that the order applies when the traffic policeman guarded the streets, but if there are no violations still occur, so it needs to enhanced surveillance and traffic control. Addressing the phenomenon that is the traffic police should understand very well about the reason why a lot going on traffic violations, both in terms of knowledge, awareness and knowledge and background conditions of local communities, to reconsider efforts to curb traffic within their fission and conditions psychic society and so it will be easier for authorities to provide guidance and bring awareness to the community. Police and the agency itself is expected to fully support the national police officers or the public in efforts to establish security and order to meet the needs of traffic, facilities in the form of facilities and infrastructure to facilitate the national police in carrying out the duties to the fullest.Keywords: Monitoring, Internal, Preventive, External